EVALUASI PENGEMBANGAN KURIKULUM MUATAN LOKAL SEKOLAH DASAR NEGERI KOTA MEULABOH - Hafinda, Tengku (AT-TA'DIB: JURNAL ILMIAH PRODI PENDIDIKAN AGAMA ISLAM, 2020)
This research was motivated by the fact that local content curriculum development in schools, was not yet optimal. This research aimed to evaluate local content curriculum development of elementary schools in Meulaboh. The main problem of this research was how the evaluation results of the development of local curriculum in Meulaboh Elementary School. This research was evaluated study using quantitative models. Evaluation is done by collecting information in the form of data component of curriculum development to then analyzed average percentage aspect by using descriptive analysis. The instruments used were questionnaires, and document observation sheets. The population consisted of 6 schools pilotting Curriculum 2013 and respondents consisted of 6 headmasters, and 19 teschers were chosen using purposive sampling technique. The results of the research indicate that: the condition of curriculum development categorized good category (59%). The results showed that over all components of the evaluation in the evaluation of each aspect of good category.